Gene transfer in higher animals: theoretical considerations and key concepts - Smith, Kevin R (J Biotechnol, 2002)
Gene transfer technology provides the ability to genetically manipulate the cells of higher animals. Gene transfer permits both germline and somatic alterations. Such genetic manipulation is the basis for animal transgenesis goals and gene therapy attempts. Improvements in gene transfer are required in terms of transgene design to permit gene targeting, and in terms of transfection approaches to allow improved transgene uptake efficiencies.